A regenerative braking energy recuperation from elevator operation in building by active rectifier - An Thi Hoai Thu Anh; Luong Huynh Duc (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Elevators- means of vertical transportation to carry people and goods are an indispensable part in offices, high-rise buildings, hospitals, commercial areas, hotels, car-parks when blooming urbanization develops worldwide. However, the level of energy consumption in elevator operation is significant, so energy saving solutions have been outlined and applied in practice. With frequent braking phases, regenerative braking energy is wasted on braking resistors. Therefore, this paper proposes regenerative braking energy recuperation method for elevator operation in building by active rectifiers enabling the braking energy to be fed back into utility grid. Simulation results conducted by MATLAB with data collected from OCT5B building-RESCO new urban area, Ha noi, Vietnam have verified saving energy of using active rectifiers replacing diode rectifiers up to 33%.